Replication Data for: Phytoplasma infection of a tropical root crop triggers bottom-up cascades by favoring generalist over specialist herbivores - Wyckhuys, Kris A.G. (2017)
We tested the hypothesis that a Candidatus Phytoplasma causing cassava witches’ broom (CWB) on cassava (Manihot esculenta Grantz) is altering species composition of invasive herbivores and their associated parasitic hymenopterans. We conducted observational studies in cassava fields in eastern Cambodia to assess the effect of CWB infection on abundance of specialist and generalist mealybugs (Homoptera: Pseudococcidae), and associated primary and hyper-parasitoid species. Fields were selected as follows: Chetborey, Changchrong (12.58275°, 106.07681°), Chetborey, Sambuk (12.64369°, 106.06290°), Prakprosab, Bang Liegh (12.35089°, 105.98528°), Snoul (12.02920°, 106.40232°). Within each site, we selected one field with high (>20%) and one field with low (0-5 %) incidence of CWB, as determined by assessing the presence of plants with typical symptoms of CWB infection (i.e., stunting, leaf yellowing, leaf and petiole proliferation). We randomly sampled four mealybug-infested plants without CWB symptoms from each field, and an additional four mealybug-infested CWB-symptomatic plants from plots with high CWB incidence (N=64; total number of samples). For each plant, we recorded infestation levels of Phenacoccus manihoti, Paracoccus marginatus, Ferrisia virgata and Pseudococcus jackbeardsleyi. Next, plant samples were transferred to a field laboratory, and kept until emergence of all parasitoid (and hyperparasitoid) wasps.